Manifestasi Somatik pada Depresi Sedang: Laporan Kasus Perempuan Usia 42 Tahun - Aqila, Putri; Prasetya , Era Catur (Riviera Publishing, 2025)
Depressive disorder is a mental disorder that can affect life emotionally, physically, socially and is often accompanied by somatic symptoms that can mislead the diagnosis, especially in middle-aged women who are prone to experiencing psychosocial stressors. Epidemiological research shows that about 10-15% of women in middle age can experience depression. and often accompanied by somatic symptoms that can mislead the diagnosis, especially in middle-aged women who are prone to experiencing psychosocial stressors. This report discusses a 42-year-old woman with moderate depressive episodes and somatic symptoms (F32.11) after losing both of her parents to Covid-19. Patients experience fatigue easily, loss of interest, difficulty sleeping with nightmares, anxiety in the afternoon or cloudy weather, decreased appetite, and physical complaints in the form of abdominal pain and heart palpitations. The diagnosis was upheld according to the criteria of PPDGJ III. Management is provided comprehensively through pharmacological therapy (fluoxetine 50 mg once a day and Merlopam 2 mg once a day) as well as non-pharmacological therapy in the form of supportive psychotherapy, family education, light exercise recommendations, and increased social interaction. This integrative approach has been proven to reduce emotional and physical symptoms, improve sleep quality, and help prevent recurrence.